2019
DOI: 10.1111/ajad.12886
|View full text |Cite
|
Sign up to set email alerts
|

Initiation Sequence of E‐Cigarette and Cigarette Smoking Among US Adolescents: A National Study

Abstract: Background and Objectives: The primary objectives were to: (1) examine the initiation sequence of e-cigarette use and cigarette smoking; (2) assess other substance use as a function of the initiation sequence of e-cigarettes and cigarettes; and (3) investigate the role of early e-cigarette initiation among US secondary school students. Methods: Data were collected via self-administered questionnaires from independent 2015 and 2016 nationally representative cross-sectional samples of 8th grade, 10th grade, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…One study found that among those who had initiated both cigarette and e-cigarette use, most initiated cigarette use before e-cigarette use. The same study also showed that the initiation pattern of e-cigarettes/cigarettes differentiates risk of other substance use among 12th graders [17]. Another study found that most e-cigarette users had initiated other substances, including cigarette use, before initiation of e-cigarettes [18].…”
Section: Implications and Contributionmentioning
confidence: 77%
“…One study found that among those who had initiated both cigarette and e-cigarette use, most initiated cigarette use before e-cigarette use. The same study also showed that the initiation pattern of e-cigarettes/cigarettes differentiates risk of other substance use among 12th graders [17]. Another study found that most e-cigarette users had initiated other substances, including cigarette use, before initiation of e-cigarettes [18].…”
Section: Implications and Contributionmentioning
confidence: 77%
“…Because the longitudinal MTF study first assesses individuals at age 18 when many individuals have already initiated alcohol use, we were unable to assess individuals who initiate alcohol at earlier ages. Previous research examining the order of initiation of substances found the most prevalent initiation sequence of e-cigarette use involved initiating other substances before e-cigarettes (McCabe et al, 2019), and that most current e-cigarette users had a history of alcohol or other substance use (Gilbert et al, 2020). Additionally, a prospective study of younger adolescents aged 12-17 found an association of e-cigarette use with subsequent alcohol use (Silveira et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 For the last five years, vaping prevalence has increased steadily such that vaping has surpassed cigarettes as the most common way to consume nicotine among youth, and presently one quarter of high school seniors are regularly vaping. [5][6][7] Originally patented by a pharmacist in China in 2003, vaping has gained in popularity internationally, and there has been an exponential growth in the number of devices, brands, and flavors on the market. 8,9 Vaping was introduced to the US markets in 2007 but only recently has there been increasing interest among public health groups and medical professionals as to the potential health effects of vaped products.…”
mentioning
confidence: 99%